Inter-relationship Between Condition Coefficient (K) of Penaeus monodon and Heavy Metals from a Brackish Water Pond - A., Mitra; T., Mandal; Y.A., Jamaddar; D.P., Bhattacharyya (Fishery Technology, 2025)
The condition coefficient (K) of Penaeus monodon, collected from a traditional brackish water system at Kanmari, about 50 km away from the city of Calcutta, during the period from March 1992 to February 1994, was estimated. During the investigation period, concentrations of heavy metals (Zn, Cu, Mn, Fe, Cr, Ni, Pb and Cd) in the ambient media (sediment and water) were determined to study the suitability of the environment for the growth and survival of the species. There was a negative correlation between the condition coefficient and the concentration of heavy metals in water.